2019
DOI: 10.3390/s19224827
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Convolutional Neural Network and Its Application in Rolling Bearing Fault Diagnosis under Variable Working Conditions

Abstract: The rolling bearing is an important part of the train’s running gear, and its operating state determines the safety during the running of the train. Therefore, it is important to monitor and diagnose the health status of rolling bearings. A convolutional neural network is widely used in the field of fault diagnosis because it does not require feature extraction. Considering that the size of the network model is large and the requirements for monitoring equipment are high. This study proposes a novel bearing fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…Considering the accuracy and running speed, we constructed our AI model based on the ShuffleNet V2 network [26, 27]. The CNN model using ShuffleNet V2 as the backbone is the most advanced lightweight model available, which has better accuracy and run faster than previous lightweight networks with the same computation condition.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the accuracy and running speed, we constructed our AI model based on the ShuffleNet V2 network [26, 27]. The CNN model using ShuffleNet V2 as the backbone is the most advanced lightweight model available, which has better accuracy and run faster than previous lightweight networks with the same computation condition.…”
Section: Methodsmentioning
confidence: 99%
“…Such studies have been widely reported in the recent literature and use many data sources; they cover management, maintenance, safety and operations [141]. Image-processing approaches for implementing automatic detection have been suggested for monitoring railway infrastructure [128], rail track maintenance [133], railway track inspections and train component inspections [142]- [152] such as the rolling bearings of trains [153].…”
Section: Related Work In Railway Systemsmentioning
confidence: 99%
“…However, training the model for diagnosing the faults requires the fault data under different loads. In the research of this paper, the generalization ability of the improved 1D-CNN under different loads was investigated and the result was compared to that of Shufflenet V2, MobileNet, ICN [29], DFCNN [30], and PFC-CNN [31]. The specific experimental contrast results are shown in Table 5 and Figure 13.…”
Section: Performances Under Different Loadsmentioning
confidence: 99%